Analisis Pesan Dakwah Pada Novel Si Anak Pemberani Karya Tere Liye - Tami, Fadillah Winda; Razzaq, Abdur; Muzaiyanah, Muzaiyanah (Journal of Innovative and Creativity, 2026)
Preaching is essentially an act of faith performed by Muslims, such as preachers, media, messages, audiences, methods, and responses. One way to carry out da'wah is by reading literary works. To ensure that da'wah can achieve its goals and objectives optimally. Literature is a product of art that discusses human values and how to use language to express life. The purpose of this research is to discover and analyze Tere Liye's novel "Si Anak Pemberani" to identify the Islamic values contained within it, such as courage, honesty, patience, responsibility, and social concern, and how these values can be used as messages of Islamic preaching in terms of faith, sharia, and morality. The method used is descriptive qualitative research with content analysis. The research results show that Tere Liye's novel "Si Anak Pemberani" predominantly contains moral messages (akhlak) such as courage, honesty, responsibility, and social concern. The novel can be categorized as da'wah bil qalam, a written medium that is effective in conveying Islamic values contextually to young readers.